Ethnic Migrations, Enclave Formation and Ethnopolitical Risks in the Russian Capital Region - Alexander V. Shustov (RUDN Journal of Political Science)
After the terrorist attack in Crocus City Hall on March 22, 2024, immigration from Asian CIS countries turned out to be one of the most acute foreign and domestic political problems in Russia. Its importance is greatly enhanced by the security threats posed by the use of migrants by external forces in their own conditions. The increase in these threats has given rise to a number of legislative initiatives to tighten migration policy and limit the influx of migrants themselves. However, the occurrence of this problem is by no means accidental, and the terrorist attack in Crocus City and a number of other similar incidents that occurred in 2024-2025 only highlighted its severity. It is no coincidence that most of the high-profile events related to migrants are clearly localized in the Russian capital region, which, due to the large capacity of the labor market, is the main object of their attraction. As a result, places of concentration of migrants (“ethnic enclaves”) have begun to form around the capital, the main difference between which and the surrounding territories is a much higher number of non-ethnic and non-cultural populations. The study attempts to identify such places based on open sources, mainly press materials, statistics from the Ministry of Internal Affairs and population censuses, as well as to analyze the ethnopolitical risks associated with them. The study showed that the emergence of enclaves is associated with the concentration of migrant workers in the localities of their employers. Migrants prefer to settle around them, first temporarily, and then permanently. Due to the higher birth rate and continued immigration in such areas, there is a change in the national composition of the population, among which the dominant ethnic groups among migrants begin to prevail. The result of the appearance of enclaves is an increase in the discontent of the local population, interethnic tension and an increase in the number of conflict situations, which leads to an increase in the risks of destabilization of the ethnopolitical situation. The situation is aggravated by the ongoing demographic explosion in the countries of Central (Central) Asia and the narrowness of national labor markets, which forces their indigenous populations to seek work abroad, mainly in Russia and its metropolitan region.